Development of Artificial Intelligence-Based E-Portfolio Learning Media to Enhance Social Studies Learning Independence for Fifth-Grade Students - Vidiani Br Sembiring; Sugiharto Sugiharto; Noni Rozaini; Dede Ruslan; Sri Yunita; Sriadhi Sriadhi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This research is driven by the identified deficiency in student learning autonomy within Grade V Social Studies, specifically concerning regional economic diversity, where traditional portfolios fail to provide timely pedagogical feedback. The study aims to develop and evaluate an Artificial Intelligence (AI)-based e-portfolio designed to enhance learning independence at UPT SD Negeri 066047 Medan. Utilizing a Research and Development (R&D) framework via the ADDIE model comprising Analysis, Design, Development, Implementation, and Evaluation the investigation involved Grade V students and employed observation, questionnaires, and documentation for rigorous data acquisition. Empirical findings indicate superior validity, with expert assessments yielding 88.57% for media and 90% for material content. Furthermore, practicality reached 91.67% from educators and 90% from learners, categorizing the tool as highly pragmatic for classroom integration. Effectiveness was substantiated by a significant improvement in learning independence scores, which surged from a baseline of 64,64% to 91.04% post-intervention. Consequently, the AI-integrated e-portfolio is established as a feasible and efficacious instructional innovation, facilitating reflective, interactive, and autonomous learning environments in elementary education. This media serves as a transformative technological alternative to conventional pedagogical instruments, aligning with the needs of modern digital-based curricula.